Enhanced growth of short stature in Ellis-van Creveld syndrome: A case report of a Saudi child - Essam Al Ageeli (Saudi Journal for Health Sciences)
This case report presents the diagnosis and management of Ellis-van Creveld syndrome (EVC) in a 20-year-old Saudi boy, highlighting the condition’s genetic basis and prevalence in consanguineous communities. The patient exhibited characteristic clinical and radiological features, including below-average height, bilateral postaxial polydactyly, and hypoplastic nails. Diagnosis was confirmed through genetic testing, revealing a nonsense homozygous mutation in the EVC2 gene. Remarkably, the absence of cardiac abnormalities allowed for the successful administration of growth hormone (GH) therapy, which led to a notable increase in height over 2 years, from 108 cm at age 12 to 122 cm at age 14. This case underscores the importance of comprehensive assessment and the potential benefits of GH therapy in EVC patients, particularly those without cardiac defects.